Internet of Things and its use in a corporate environment - Hausteinová, Iveta; Topolová, Ivana; Kubálková, Markéta, 1970-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This thesis focuses on phenomenon of the Internet of Things. It consists of 4 chapters. First chapter is focused on the introduction of IoT and the technolohies that are used within this concept. Next chapter is about IoT in the Czech Republic and application cases.
Vedoucí práce: Ivana Topolová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses